PENINGKATAN KOMPETENSI BERBAHASA ARAB SISWA MELALUI MODEL MANAJEMEN PEMBELAJARAN POACE - Setiawan, Hasrian Rudi; Mukti, Abd.; Syaukani, Syaukani (Arabi : Journal of Arabic Studies, 2021)
This study aimed to explain the improvement of students' Arabic competence through the POACE learning management model. This research is a field research, using qualitative research methods. Data collection techniques in this study used interviews, observations, and documentation. The technique used to ensure the validity of the data is triangulation. This study uses data analysis with Miles Huberman's interactive analysis model, namely collection data, reduction data, display data, conclusion: drawing/verification. The results showed that the POACE learning management model as an effort to improve students' Arabic competence was carried out with the following stages of activites: 1) Planning, namely determining achievement targets and how to carry out these activities; 2) Organizing, namely making arrangements for the resources owned; 3) Carrying out (action), namely learning activities are carried out in accordance with the planned procedures; 4) Control, which is to supervise all learning activities; 5) Evaluating, namely measuring the achievement of learning activities.